Karakterisasi Bakteriologis Dalam Air Minum Isi Ulang dan Air Minum Dalam Kemasan - Fajriah, Siti; Haniarti, Haniarti; Umar, Fitriani; Sari, Rasidah Wahyuni (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Most of the human body consists of water and humans as living creatures certainly need water for survival. A very important use of water is for drinking. Therefore, drinking water must meet health requirements, in accordance with the Republic of Indonesia Minister of Health Regulation No: 492/MenKes/Per/IV/2010 that the requirements for good drinking water quality must meet several parameters, namely microbiological, namely 0/100 ml, physical, and chemistry. This research aims to find out whether refillable water and bottled drinking water in Takkalasi Village is contaminated with Coliform and Escherichia coli bacteria. This research is descriptive in nature with a quantitative approach through observation and taking and examining water samples in the laboratory. The research test results showed that all samples from the MS depot, Ameera RO depot, and Al Barru depot met the requirements for drinking water quality standards. It was concluded that refilled drinking water and bottled drinking water in Takkalasi Village were suitable for consumption because they were not contaminated with Coliform bacteria and Escherichia coli or fecal Coli which had met the maximum permitted levels for Coliforms in drinking water. is 0. The conclusion and recommendation is that, from the results of laboratory tests using the Most Probable Number method, it can be seen that all samples of refillable drinking water and bottled drinking water have met the requirements applied by the Republic of Indonesia Minister of Health Regulation No. 492/Menkes/IV/2010 concerning Drinking Water Quality Requirements, namely that all samples do not contain E.coli and Coliform bacteria. It is hoped that drinking water depot owners will be more selective in choosing services providing raw water sources, if necessary, the depot manager will have a written proof of receipt of raw water purchase from a water transportation company/water source certificate. Keywords: Coliforms; Escherichia coli; Drinking Water